Measuring unemployment insurance generosity - Stéphane Pallage; Lyle Scruggs; Christian Zimmermann (Institute for the Study of Labor (IZA), 2008)
In this paper, we develop a methodology to summarize the various policy parameters of an unemployment insurance scheme into a single generosity parameter. Unemployment insurance policies are multdimensional objects. They are typically defined by waiting periods, eligibility duration, benefit levels and asset tests when eligible, which makes intertemporal or international comparisons difficult. To make things worse, labor market conditions, such as the likelihood and duration of unemployment matter when assessing the generosity of different policies. We build a first model with such complex characteristics. Our model features heterogeneous agents that are liquidity constrained but can self-insure. We then build a second model that is similar, except that the unemployment insurance is simpler: it is deprived of waiting periods and agents are eligible forever with constant benefits. We then determine which level of benefits in this second model makes agents indifferent between both unemployment insurance policies. We apply this strategy to the unemployment insurance program of the United Kingdom and study how its generosity evolved over time.
urn:nbn:de:101:1-20081216222
Keywords: E24; 330; Unemployment insurance; labor market policy evaluation; Arbeitslosenversicherung; Lohnersatzleistungen; Haushaltsökonomik; Sozialtransfer; Messung; Vergleich; Theorie; Großbritannien